Analisis Kebisingan Pada Carnel Station Untuk Meningkatkan Kenyamanan Bekerja Pt.Anugrah Fajar Rezeki - Furqan, Furqan; Andriani, Meri (Program Studi Teknik Industri, Fakultas Teknik. Universitas Samudra, 2023)
Noise in the industrial work environment is one of the risk factors that can affect worker comfort and productivity. This study aims to analyze the level of disturbance at the Carnel Station at PT. Anugrah Fajar Rezeki in order to improve comfort and work safety. The methodology used includes measuring the intensity of disturbance using a Sound Level Meter (SLM) at several strategic points during factory operating hours. The data obtained are analyzed based on the applicable threshold value (NAB) standards and the maximum exposure time to disturbance is calculated using the NIOSH (National Institute for Occupational Safety and Health) formula. The results of the study indicate that the level of disturbance at several points exceeds the established NAB, potentially disrupting worker comfort and health. Therefore, it is recommended to use personal protective equipment such as earplugs and earmuffs, as well as the implementation of a work rotation system to minimize exposure to disturbances on an ongoing basis. The implementation of this recommendation is expected to create a safer and more comfortable work environment for workers.